Computer-Based Corpus Analysis of Lexical Changes in Contemporary Indonesian: A Diachronic Study on Online Mass Media - Fatimah, Siti; Gonzales, Samantha; Ramos, Nathaniel (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid evolution of language in the digital age has led to significant lexical changes in contemporary Indonesian, particularly in online mass media. The rise of digital platforms, social media, and internet-based communication has contributed to the rapid development of new vocabulary, slang, and expressions. This study aims to analyze these lexical changes over time, focusing on their manifestation in Indonesian online mass media. By using computer-based corpus analysis, the research investigates how language evolves within this digital context, identifying the frequency, usage, and context of newly coined terms and shifting meanings. The research employs a diachronic approach, analyzing a corpus of Indonesian online news articles and social media posts from the last two decades. The study focuses on lexical items that have emerged or significantly changed in meaning during this period. Through computational tools such as natural language processing (NLP), the study tracks these lexical shifts and examines their social and cultural implications. The findings show a marked increase in the adoption of digital and globalized terms, as well as the reshaping of traditional Indonesian vocabulary to reflect contemporary issues and technological advances. The study concludes that online mass media plays a critical role in shaping contemporary language and accelerating lexical change in Indonesian.